Modal Analysis of Medium Calibre Barrels - Peter LISÝ (Wojskowa Akademia Techniczna, 2019)
The paper deals with modal analysis of the two different medium calibre barrel weapons. At present time PC software which are based on FEM modal analysis enable not only create a new design but also check old design how be up to standard on the fire accuracy. Also, at this time is big boom to make new armour personal carriers which are equipped with the medium weapon calibre systems. Many of them use standard design of bedding the barrel to the weapon case, however also they are created in new weapon design. The modal analysis is powerful method to describe their vibration properties which have the cardinal influence on the accuracy of fire. The barrels were modelled as 3-D objects with next configuration with aim to obtain right results and their mutual comparison. Figures 1-3 show design of the solved barrels. Modal analysis was performed by LS-DYNA software using iterative Lanczos method. In Tables 1-5, the natural frequencies for these barrels and their modifications and their corresponding own shapes are listed. Next Figures 4, 7-10, 12 show the courses natural frequencies versus modes. In Figure 11 are shown the modal shapes of the modified cylindrical weapon barrel with the armature.
Keywords: Analiza drgań lufy podczas strzału